ANALISIS PENERAPAN METODE ONE WAY ANOVA MENGGUNAKAN ALAT STATISTIK SPSS - Dewi, Sevita Sari; Ermina, Rizka; Kasih, Veilla Anggoro; Hefiana, Fera; Sunarmo, Agus; Widianingsih, Rini (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2023)
This article describes the statistical procedure for identifying significant differences between groups using one-way analysis of variance. The SPSS statistical programme employs this methodology. In order to ascertain mean differences among three or more independent groups, one-way analysis of variance is employed. This capability enables researchers to ascertain whether at least one group exhibits noteworthy variations. The sequential procedure for utilising the one-factor ANOVA method in SPSS is explicated in this article, encompassing the identification of a suitable model and the interpretation of the outcomes. In light of this, the purpose of this article is to offer researchers and professionals interested in utilising SPSS statistical tools to analyse differences between groups via the one-way ANOVA statistical method with actionable advice.